2019
DOI: 10.1136/bmjopen-2019-029796
|View full text |Cite
|
Sign up to set email alerts
|

Editors’ and authors’ individual conflicts of interest disclosure and journal transparency. A cross-sectional study of high-impact medical specialty journals

Abstract: ObjectiveTo assess the fulfilment of authors’ and editors’ individual disclosure of potential conflicts of interest in a group of highly influential medicine journals across a variety of specialties.DesignCross-sectional analysis.Setting and participantsTop-ranked five journals as per 2017 Journal Citation Report impact factor of 26 medical, surgery and imaging specialties.InterventionsObservational analysis.Primary and secondary outcome measuresPercentage of journals requiring disclosure of authors’ and edito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…It is encouraging to see that the majority of pain journals satisfied all four requirements for the ICMJE disclosure of conflicts of interest. This finding is consistent with Dal-Ré et al 42 that showed 99% of 130 highest ranked medical specialty journals require authors to disclose conflicts of interest. However, author adherence to reporting conflict of interests, reliability of the self-reporting and what conflicts should be disclosed remains an unresolved and significant problem in medical research 43.…”
Section: Discussionsupporting
confidence: 91%
“…It is encouraging to see that the majority of pain journals satisfied all four requirements for the ICMJE disclosure of conflicts of interest. This finding is consistent with Dal-Ré et al 42 that showed 99% of 130 highest ranked medical specialty journals require authors to disclose conflicts of interest. However, author adherence to reporting conflict of interests, reliability of the self-reporting and what conflicts should be disclosed remains an unresolved and significant problem in medical research 43.…”
Section: Discussionsupporting
confidence: 91%
“…Such editorial biases also relate to issues of epistemic diversity within the editorial process itself, which can lead to knowledge homogenisation, a perpetuation of the 'Matthew effect' in scholarly research [52,53] and inequities in the diffusion of scientific ideas [54]. These issues are further exacerbated by the fact that editors often fail to disclose their conflicts of interest, which can be viewed as compromising their objectivity [55,56], and the extent to which editors treat their reports seriously, as well as any dialogue between them and reviewers and authors [57]. For example, how an editor might decide to signal to authors which reviewer comments are more important to address and which can be overlooked and consequently, how authors might then deal with these.…”
Section: Roles Of Editors In Peer Reviewmentioning
confidence: 99%
“…Another study of websites of 130 top specialty medical journals in 2018 showed that only 45% endorsed the ICMJE recommendations and 12% disclosed individual editors’ COIs whereas 99% required authors to disclose their COIs (table 1). 7 In this study, 69% of the journals were linked to a professional organisation (society, association, or college) or a public institution7; the professional community and the public expect such institutions to be transparent about their work, including journal publication.…”
Section: Transparency Of Editor’s Financial Interestsmentioning
confidence: 96%
“…This is despite it being an ICMJE member 8. Similarly, prominent journals linked to public health organisations like Eurosurveillance from the European Centre for Disease Prevention and Control (ECDC), and Emerging Infectious Diseases and Morbidity Mortality Weekly Report from the US Centers for Disease Control and Prevention, do not disclose their editors’ COIs 7. Whereas payments to some journal editors have been reported in the US because of the existence of a national database on industry payments to physicians,1011 there are few reports on industry payments to healthcare professionals in other countries12131415 and none regarding payments to journal editors.…”
Section: Transparency Of Editor’s Financial Interestsmentioning
confidence: 98%
See 1 more Smart Citation